Fetal Radiology A Diagnostic Atlas - Schumacher, Reinhard; Seaver, Laurie H.; Spranger, Jürgen (Springer Berlin Heidelberg, 2004)
Intrinsic errors of skeletal development are individually rare but of clinical importance because of their overall frequency and their impact on a patient's life. Sonography has become a routine component of prenatal care, and many of these disorders are diagnosed prenatally. Postnatally, the prenatal diagnosis has to be verified. To this end, fetal radiography is an effective, simple and economic way to establish a diagnosis or to narrow the number of diagnostic possibilities sufficiently to enable pathological, biochemical or molecular studies to be used in the quest for a specific diagnosis. Equally important, a correct diagnosis is required for correct prognostication and parental counseling. This book has been written to assist in the postnatal diagnosis of fetal errors of skeletal development
Keywords: Pediatrics; Diagnostic Radiology; Obstetrics/Perinatology/Midwifery; Gynecology; Radiology, Medical; Obstetrics; Medizinische Radiologie; Radiologische Diagnostik; Fetus; Fetopathie; Atlas